Ethics at the workplace - Blum, Albert A. (Journal of business ethics, 1988)
Are facts the only criteria that should determine an arbitrator's decision but are there other ethical criteria that ought to be used? Arbitrators are often faced with deciding issues like whether a person discharged already by a company for arson, should be reinstated or not to his old job. The problem, however, may not be the facts but that the company has discharged him to get rid of him so that it no longer has a problem while society does with the arsonist at work elsewhere., Another problem involves the teaching of human resources management. Most of the current literature dealing with modern management reflects the belief that participatory management is good for management. Most of the evidence supporting such a claim is weak; there surely is very little evidence that such participation should include nonsupervisory employees. The discussion concerning the issue of participatory management could be raised if the participants stopped talking about the increased productivity that is supposed to result, but rather deal instead with the issue that such participation is a form of industrial democracy and therefore is good or bad depending upon a person's ethical judgments concerning such an issue.